Option pricing and implied volatilities in a 2-hypergeometric stochastic volatility model - Privault, Nicolas (2017)
We derive closed-form analytical approximations in terms of series expansions for option prices and implied volatilities in a 2-hypergeometric stochastic volatility model with correlated Brownian motions. As in Han et al. (2013), these expansions allow us to recover the well-known skew and smile phenomena on implied volatility surfaces, depending on the values of the correlation parameter.